Proffer for the implementation of the SLP method and automation in a poultry plant for process optimization - Saravia De La Cruz, Jeremy Emmanuel (2025)
This research analyzes the distribution of a poultry plant, with defined processes and established areas. However, it has been proven that the poultry production process can optimize its processes by redistribu ting it, applying the SLP (Systematic Layout Plan- ning) methodology. In addition, the purpose is to take the process to a second level of improvement with process automation. Initially, the plant plans were analyzing in detail, these allowed us to visualize which areas should be improved. Then, the DAP (Process Activity Diagram) was analyzed, where the activities are identified for the plant process. Thereafter, the SLP method is applied, which is essential for the redistribution of the plant. Once a more ef ficient plant has been obtained, productivity is analyzed using a distance and load matrix. Furthermore, the idea of automation in important processes is shown in a cost and time table. Finally, a DAP is developed that gives validity to this proposal.